Assessing access to MRI of patients with magnetic resonance-conditional pacemaker and implantable cardioverter defibrillator systems: the Really ProMRI study design. Issue 10 (October 2015) - Maglia, Giampiero; Curnis, Antonio; Brieda, Marco; Anaclerio, Matteo; Caccavo, Vincenzo; Bonfanti, Paolo; Melissano, Donato; Caravati, Fabrizio; Giovene, Lisa; Gargaro, Alessio
Abstract : Background: Despite the fact that magnetic resonance (MR)-conditional pacemaker and lead systems have been introduced more than 5 years ago, it is still not clear whether they have actually facilitated the access of pacemaker patients to this important diagnostic tool. Factors limiting MR scans in daily practice in patients with MR-conditional cardiac implantable electronic device (CIED) systems may be related to organizational, cultural and sometimes legal aspects. The Really ProMRI registry is an ongoing survey designed to assess the annual rate of MR examinations in patients with MR-conditional implants, with either pacemakers or implantable cardioverter defibrillators, and to detect the main factors limiting MRI. Methods: The primary endpoint of the Really ProMRI registry is to assess the current access to MRI of patients with MR-conditional pacemaker or implantable cardioverter defibrillator systems during normal practice. Data in the literature reported a 17% annual incidence of medical conditions requiring MRI in CIED patients. The Really ProMRI registry has been designed to detect 4.5% absolute difference with an 80% statistical power, by recruiting 600 patients already implanted with MR-conditional CIED implant. Patients will be followed up for 1 year, during which they will be asked to refer any prescription, execution or denial of an MR examination by patient questionnaires and original source documents. Conclusion: The ongoing Really ProMRI registry will assess the actual rate of and factors limiting the access to MRI for patients with MR-conditional CIEDs.